Une figurine de type métapontin dans la collection Berne-Malibu-Copenhague - Eukene Bilbao Zubiri (Les Carnets de l’ACoSt)
This paper presents a figurine from the Berne-Malibu-Copenhagen collection, looted in southern Italy in the 1970s and 1980s and now held at the Museo nazionale archeologico della Sibaritide. Examined as part of the complete publication of this collection, currently in preparation, the piece is characterised by its morphological originality. The moulded type was created in Metapontion at the end of the 7th century B.C.E., but the manufacturing technique combining a moulded front and a modelled back has no exact parallel in this polis or in neighbouring settlements. Its provenance cannot be determined at the moment, but it is an original example of the diversity of manufacturing processes used by the first moulding craftsmen in Magna Graecia.